Small States in World Politics: State of the Art - Radoman, Jelena (Journal of Regional Security, 2019)
In the literature review to follow I will rst provide an overview of the major e orts in small states studies, concerning most importantly the de nition of ‘smallness’ as the area in which an agreement is yet to be reached. is will be followed by an overview of the scholarly discussions on smallness and power and strategies that small states employ to mitigate their material limitations, which have led scholars to question the concept of power. is raised the following question: are small states permanently locked into a power hierarchy which they cannot escape, or do they have a possibility to overcome their material limitations by shaping and re-shaping relations in which they are found? Constructivists moved the debate away from structural variables and limitations that these states are faced with, and brought into the picture the small states’ possibilities and di erent roles they might employ, thus bypassing the limitations emerging from the ‘small vs. big powers’ dichotomy. eories of alliances, however, continue to picture the choices that are presented to small states as only two: to seek protection of bigger states or risk standing alone. Least work has been done on where and how smallness matters and where opportunities for small states lie. Future work should re ect if, when, and how ‘smallness’ is a factor in these states’ foreign policies and their alignment politics.